Choledochal cyst with aberrant right posterior duct - Mridul Prasad Joshi; A.K.M. Zahid Hossain (Elsevier, 2020)
Choledochal malformation, previously known as "choledochal cyst" is the congenital dilatation of any portion of the biliary tree. Its incidence varies from 1 in 48,000 in UK to 1 in 1000 in Japan. Type 1 is the most common one. Surgical options include total cyst excision with roux en Y hepaticojejunostomy or hepaticoduodenostomy for type 1. Detailed knowledge about normal extrahepatic biliary tract and its variations is needed to prevent complications. These aberrations of the anatomical structures of vascular and ductal structures make any hepatobiliary surgery challenging to surgeons. The normal configuration is present in around 60% of the population. We report a rare case of choledochal cyst patient in which there was a right posterior duct aberration with double cystic ducts and one of the cystic ducts opened into the distal portion of aberrant duct. There was a need for double anastomosis of hepaticojejunostomy rather than one, as ligating the aberrant duct would have caused segmental cirrhosis and later atrophy. Failure to identify the aberrant vessel would have caused prolonged bile leakage in the postoperative period. Therefore, assessment of the biliary anatomy and identification of normal variants are challenging points in the surgical planning.